Development of Supply Chain Management and Economic Transition from Recession Crisis, and Uncertain Conditions - A. Udovikova, Alla; N. Marchenkova, Irina (International Journal of Supply Chain Management, 2020)
In an uncertain recovery, supply chain operations need to be more scalable and flexible as they anticipate economic recovery and increase capacity. Moreover, this can be easier to achieve coming out of a severe recession. The relevance of econometric related to the verification of supply chain management accounting is primarily due to the fact that violations in supply chain management can lead to significant negative financial consequences for an economic entity. In addition, the management of the organization that committed supply chain management offenses regarding the timeliness and accuracy of the calculation and payment of supply chain managements and insurance premiums bears, in accordance with the current legislation of the Russian Federation, administrative and criminal liability. All this increases the importance and role of this type of service in the structure of economic activity, as a supply chain management economic. However, at present, the concept of supply chain management economic does not have clear regulation, due to the lack of relevant regulatory acts defining the methodology for its implementation.